Дослідження впливу локальних деформацій поверхні на амплітуду кореляційного сигналу у процесі обробки зображень - Максименко, О.П.; Нечипорук, С.А.; Ільчишин, Б.Д. (Фізико-механічний інститут ім. Г.В. Карпенка НАН України, 2010)
The model of a correlation signal for non-coherent speckles is offered and quantitative ratio between value of deformations and amplitude of cross-correlation peak with taking into account the dimension of non-coherent speckles and their quantities in an image fragment are established.